Preventing Acute Kidney Injury: a qualitative study exploring 'sick day rules' implementation in primary care. Issue 1 (December 2016) - Morris, Rebecca; Ashcroft, Darren; Phipps, Denham; Bower, Peter; O'Donoghue, Donal; Roderick, Paul; Harding, Sarah; Lewington, Andrew; Blakeman, Thomas
Abstract Background In response to growing demand for urgent care services there is a need to implement more effective strategies in primary care to support patients with complex care needs. Improving primary care management of kidney health through the implementation of 'sick day rules' (i.e. temporary cessation of medicines) to prevent Acute Kidney Injury (AKI) has the potential to address a major patient safety issue and reduce unplanned hospital admissions. The aim of this study is to examine processes that may enable or constrain the implementation of 'sick day rules' for AKI prevention into routine care delivery in primary care. Methods Forty semi-structured interviews were conducted with patients with stage 3 chronic kidney disease and purposefully sampled, general practitioners, practice nurses and community pharmacists who either had, or had not, implemented a 'sick day rule'. Normalisation Process Theory was used as a framework for data collection and analysis. Results Participants tended to express initial enthusiasm for sick day rules to prevent AKI, which fitted with the delivery of comprehensive care. However, interest tended to diminish with consideration of factors influencing their implementation. These included engagement within and across services; consistency of clinical message; and resources available for implementation. Participants identified that supporting patients with multiple conditions, particularly with chronic heart failure, made tailoring initiatives complex. Conclusions Implementation of AKI initiatives into routine practice requires appropriate resourcing as well as training support for both patients and clinicians tailored at a local level to support system redesign.